The Clinical Frailty Scale (CFS) employment in the frailty assessment of patients suffering from Non-Communicable Diseases (NCDs): A systematic review - Granata, Nicolò; Vigoré, Martina; Steccanella, Andrea; Ranucci, Luca; Sarzi Braga, Simona; Baiardi, Paola; Pierobon, Antonia (Frontiers in Medicine, 2022)
Background: The Clinical Frailty Scale (CFS) is a well-established tool that has been widely employed to assess patients’ frailty status and to predict clinical outcomes in the acute phase of a disease, but more information is needed to determine the impact of this tool when dealing with Non-Communicable Diseases (NCDs). Methods: An electronic literature search was performed on PubMed, Medline, Scopus, EMBASE, Web of Science, and EBSCO databases to identify studies employing the CFS to assess frailty in patients with NCDs. Findings: After database searching, article suitability evaluation, and studies’ quality assessment, 43 studies were included in the systematic review. Researches were conducted mostly in Japan (34.88%), and half of the studies were focused on cardiovascular diseases (48.84%), followed by cancer (23.26%), and diabetes (11.63%). Simplicity (32.56%), efficacy (30.23%), and rapidity (13.95%) were the CFS characteristics mostly appreciated by the authors of the studies. The CFS-related results indicated that its scores were associated with patients’ clinical outcomes (34.88%), with clinical decision making (11.63%) and, with the presence of the disease (11.63%). Furthermore, CFS resulted as a predictor of life expectancy in 15 studies (34.88%), clinical outcomes in 8 studies (18.60%), and hospital admissions/readmissions in 4 studies (9.30%). Discussion: CFS was found to be a well-established and useful tool to assess frailty in NCDs, too. It resulted to be related to the most important disease-related clinical characteristics and, thus, it should be always considered as an important step in the multidisciplinary evaluation of frail and chronic patients.